Avaliação do potencial genotóxico de produtos comerciais contendo carbendazim ou tebuconazol utilizando Teste de Micronúcleo em Tradescantia pallida - Ghisolfi, Magali (2020)
Plant foods are essential to the human diet and their productivity is increased with the application of pesticides in crops. One of the most widely used classes of pesticides includes fungicides, which can be used on plantations or on food already harvested. However, these compounds do not only affect fungi but also cause damage to the environment and human health. Commercial products containing pesticides have in their formulations substances that can alter the toxic effects of the active ingredients, so it is essential to carry out the toxicity assessment of these compounds. The use of plants, such as Tradescantia pallida, in genotoxicity tests has shown great potential due to its low cost, simplicity and sensitivity. The objective of the present study was to evaluate the genotoxic potential of the commercial formulations Bendazol® and Folicur® EC 200, containing tebuconazole and carbendazim respectively at levels equal to or below the maximum limits allowed in food, using the Micronucleus Test in Tradescantia pallida. Inflorescences of the plant were exposed to concentrations of 0.005 and 0.5 ppm of carbendazim and 0.007; 0.07 and 0.7 ppm of tebuconazole. Sodium azide was used as positive control and distilled water as negative control. The visualization of the micronucleus in the tetrads was performed with a microscope, after the anthers were fixed in a solution of acetic acid/ethanol (1:3 v/v) for 24 hours. The number of micronucleus was determined and expressed as the frequency of micronucleus formation per 1500 tetrads. The results indicated that carbendazim did not show a significant effect on the formation of micronucleus in relation to the negative control. However, tebuconazole concentrations 0.07 and 0.7 ppm increased the formation of micronucleus, showing genotoxic potential at doses below or equal to the maximum residue limit in tomatoes. This result proves the sensitivity of the Trad-MCN Test, since it detected a genotoxic effect in concentrations below 1 ppm. This is the first study to assess the genotoxic potential of the fungicides carbendazim and tebuconazole using the Micronucleus test in Tradescantia pallida at such low levels, which are allowed in foods in several countries.